A preliminary study of pulmonary vein implant applicability and safety as a potential ablation platform in a follow‐up study in pigs. Issue 2 (24th January 2018) - Vandecasteele, Tim; Schauvliege, Stijn; Philpott, Matthew; Clement, Eli; van Loon, Gunther; Vera, Lisse; Boussy, Tim; van Bergen, Thomas; Van Den Broeck, Wim; Cornillie, Pieter; Van Langenhove, Glenn
Abstract: Background: Recurrence of atrial fibrillation after an ablation procedure remains a major problem which emphasizes the need for improved pulmonary vein isolation techniques. Aims: The aim of this study was to describe an implantation procedure of a pulmonary vein‐stent which may possibly serve as an ablation technique in the future and to examine stent safety in a follow‐up study in pigs. Methods and results: Eight pigs were catheterized and nine self‐expanding nitinol stents were implanted through a transfemoral or transatrial approach into the antra of the pulmonary veins. After 3 months' follow‐up, the animals were euthanized for further examination. During the follow‐up phase, no complications were observed. Absence of thrombus formation or pulmonary vein wall dissection was noticed during anatomical and histological evaluation of the heart‐lung packages. All implants were almost completely covered by neo‐intima, of which thickness varied between 0.2 and 3.9 mm. Conclusions: Stents can safely be positioned and deployed into the antra of the pulmonary veins without any acute or long‐term (3 months) adverse effects. In the future, these implants could function as a permanently implanted ablation device and provide new therapeutic strategies for pulmonary vein isolation in patients with atrial fibrillation.